The Effect of Student Attitudes on Mathematical Understanding Ability in Mathematical Logic in Hybrid Learning - Hikmah, Rezkiyana; Rejeki, Sri; Tama, Bayu Jaya (Pendidikan Matematika STKIP Kusuma Negara, 2023)
This studi aims to determine the effect of students’ attitudes on learning outcomes of mathematical logic and to determine how much influence students’ attitudes have on learning outcomes of mathematical logic The research sample consisted of third semester students of the computer science engineering program who took the mathematical logic course. The result obtained are that there is an effect of attitude on the learning outcomes of student mathematical logic. The result of the regression model obtained with the value of F count = 7.055 with a significance level of 0.009 < 0,005 with indicates that there is an effect of attitude on the learning outcomes of mathematical logic. The result of the correlation value r is 0.231 and the coefficient of determination (R square) is 0.053 which shows that the effect of the independent variable (attitude) on the dependent variable (learning outcomes of mathematical logic) is 5.3%. This shows that there is a positive influence of students’ attitudes on students’ learning outcomes in mathematical logic.